2018
DOI: 10.1016/j.trsl.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Image analysis and machine learning for detecting malaria

Abstract: Malaria remains a major burden on global health, with roughly 200 million cases worldwide and more than 400,000 deaths per year. Besides biomedical research and political efforts, modern information technology is playing a key role in many attempts at fighting the disease. One of the barriers toward a successful mortality reduction has been inadequate malaria diagnosis in particular. To improve diagnosis, image analysis software and machine learning methods have been used to quantify parasitemia in microscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
271
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 417 publications
(280 citation statements)
references
References 89 publications
1
271
0
8
Order By: Relevance
“…It is customary to provide a comparison of results for a proposed method vs other methods in the literature. This is problematic here because, as discussed in [9] most studies do not give patient-level results, due to data limitations and/or chosen methodologies. For example, if a method used a train/val split that allows a sample's objects into both train and validation, or if it did not report patient-level results, then its results are not comparable to ours.…”
Section: B Comparison To Other Methodsmentioning
confidence: 99%
“…It is customary to provide a comparison of results for a proposed method vs other methods in the literature. This is problematic here because, as discussed in [9] most studies do not give patient-level results, due to data limitations and/or chosen methodologies. For example, if a method used a train/val split that allows a sample's objects into both train and validation, or if it did not report patient-level results, then its results are not comparable to ours.…”
Section: B Comparison To Other Methodsmentioning
confidence: 99%
“…Usually, the initial step of CAD is the acquisition of digital images of blood smears. This initial step breaks down the different approaches for the differenty types of microscopy, blood slides (thin or thick) and staining [14].…”
Section: D) Rapid Diagnostic Tests (Rdt)mentioning
confidence: 99%
“…As a result, the algorithms used were revealed that CNN's RAN model was not used and this model was preferred in our study Algorithms such as Thresholding (IM), KNN, BN, Decision tree, Convolutional Neural Network (CNN) were used in these processes, also a new method has been established to identify the presence of malaria parasites image processing techniques and Support Vector Machine (SVM) and using (ANN) algorithms were used to classification malaria diseases moreover, VGG16-SVM outperforms existing CNN models in all performance indicators such as accuracy, precision, specificity and precision. As a result, the algorithms used were revealed that CNN's RAN model was not used and this model was preferred in our study [5][6][7][8][9][10][29][30]. However, to the best of our knowledge, no attention mechanisms have been applied to building feed forward networks to achieve the most advanced results in image classification tasks.…”
Section: Introductionmentioning
confidence: 99%